Power decoupling method for synchronous reference frame-based vector control - Gong, Zhen; Xie, Xiaorong; Liu, Chengxi; Faria da Silva, Filipe; Gui, Yonghao (International journal of electrical power & energy systems, 2025)
•Real and reactive powers coupling of VSI vector control cannot be neglected when VSI connects to weak grids.•When real power increases, VSI will absorb coupling reactive power from power grids, which may cause instability.•The proposed method can reduce power coupling magnitudes in transient and quasi-steady state. This short communication analyzes the power coupling mechanism of synchronous reference frame-based vector control (SRF-VC) of voltage source inverter (VSI), which is caused by the variation of voltage angle difference (VVAD) between voltage at point of common coupling (PCC) and grid voltage. Then, a power closed loop transfer function model is proposed to study the power coupling characteristics. It reveals that when there is an increase of output real power, the VSI will absorb coupling reactive power from power grids which will limit its real power transfer capability and even cause transient instability. Next, a power decoupling strategy for SRF-VC is proposed based on a dynamic feedforward power compensation (DFPC) algorithm, and its power decoupling capability is analyzed based on the transfer function. Simulations and experimental results show that the proposed method can not only reduce power coupling magnitudes in transient stage, but also realize power ripple cancellation in quasi-steady state.